2008
DOI: 10.1080/15435070802229068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Kinetics and Mechanism Involved in the Biosorption of Heavy Metals on Activated Sludge

Abstract: An investigation has been undertaken to determine the removal of heavy metals (Cd 2+ , Cu 2+ , Ni 2+ and Zn 2+ ) of high environmental priority due to their toxicity from dilute aqueous solutions by biosorption using inexpensive biomaterials like activated sludge. Activated sludge is used widely in water treatment plants and is easily available. Each experiment was performed over a period of time to determine the biosorption of heavy metals from the aqueous phase to the solid phase. The maximum sorption uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
4
20
0
1
Order By: Relevance
“…A decrease in the sorption capacity at higher speed of agitation may be attributed to improper contact between the dye ions and the binding sites on the biomass, as the suspension is no longer homogenous due to vortex formation, which makes the adsorption of dye ions difficult [38,39]. The effect of contact time on the removal of RO 13 dye indicated that a longer contact time favored the reaction toward the equilibrium Locating the region of optimum response by the PSA In the current investigation, PSA was employed to move from the current operating conditions to the optimum region in the most efficient way by using the minimum number of experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in the sorption capacity at higher speed of agitation may be attributed to improper contact between the dye ions and the binding sites on the biomass, as the suspension is no longer homogenous due to vortex formation, which makes the adsorption of dye ions difficult [38,39]. The effect of contact time on the removal of RO 13 dye indicated that a longer contact time favored the reaction toward the equilibrium Locating the region of optimum response by the PSA In the current investigation, PSA was employed to move from the current operating conditions to the optimum region in the most efficient way by using the minimum number of experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Each node in the input layer represents the value of one independent variable, while the output nodes indicate the dependent variables [38]. The model consisted of three layers: an input layer with four neurons (initial pH, dye concentration, biosorbent dosage and speed of agitation), a hidden layer with three neurons and an output with one neuron (4-3-1).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…pH was adjusted throughout the runs around 4 which is an optimum value (Farah, et al, 2007;Tunali et al, 2006) since at low pH values the biosorption of metals decreases because of competition for binding sites between ions and protons, while at pH higher than 6, solubility of metal complexes decreases sufficiently allowing precipitation, which may complicate the sorption process and do not bind to the adsorption sites on the surface of the biomass. After 4-7 hrs of agitation which is enough to reach equilibrium (AjayKumar et al, 2009), the solution was filtrated using filter paper type (Wattmann no. 4) and a sample of (2 ml) was taken for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These advantages have served as the primary incentives for developing full-scale biosorption process to clean up heavy-metal pollution (AjayKumar et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al (1991) also agreed with result while using tamarind seed for adsorbing cadmium [44].However the adsorption was found to be low at 200 rpm (40. ) using activated sludge [45]. As the shaking speed 150 rpm was sufficient to ensure the availability of all the binding 2.…”
Section: Effect Of Agitation On Adsorptionmentioning
confidence: 99%